1997
DOI: 10.1021/ic970062z
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis and Characterization of the Chiral Complexes cis- and trans-[Ru((SS)-Pripybox)(py)2Cl]PF6 and [Ru((SS)-Pripybox)(bpy)Cl]PF6

Abstract: The chiral oxazoline complexes cis- and trans-[Ru((SS)-Pr(i)pybox)(py)(2)Cl]PF(6) were prepared from the common precursor trans-[Ru((SS)-Pr(i)pybox)(py)Cl(2)], and all three complexes were spectroscopically and structurally characterized. The complex cis-[Ru((SS)-Pr(i)pybox)(py)(2)Cl]PF(6) crystallized in P2(1)2(1)2(1) with Z = 4, a = 8.396(2) Å, b = 18.396(3) Å, c = 20.954(3) Å, and R = 0.039 for 4131 reflections. The complex trans-[Ru((SS)-Pr(i)pybox)(py)(2)Cl]PF(6) crystallized in P2(1) with Z = 2, a = 10.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…33,34 The aqua complexes [Ru(OH 2 )L 5 ] n+ are of particular interest, as their 2e oxidation can give oxo complexes of the type [Ru IV (O)L 5 ], which have been used in a number of stoichiometric and catalytic oxygen-transfer reactions with alkanes, 35 alkenes, 2c,36,37 alcohols, 38 phosphines, 39 and sulfides. 40 The electrochemistry of aqua complexes of ruthenium(II) has been investigated in great detail by Meyer, 37 Che, 41 and Takeuchi. 42 Thus, the aqua complex [RuCl(OH 2 )(1a-κ 4 P,N,N,P)] + (3a) is possibly related to the hypothetical ruthenium(IV) oxo species [RuCl(O)(1a-κ 4 P,N,N,P)] + , the putative intermediate in the catalytic epoxidation described below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 The aqua complexes [Ru(OH 2 )L 5 ] n+ are of particular interest, as their 2e oxidation can give oxo complexes of the type [Ru IV (O)L 5 ], which have been used in a number of stoichiometric and catalytic oxygen-transfer reactions with alkanes, 35 alkenes, 2c,36,37 alcohols, 38 phosphines, 39 and sulfides. 40 The electrochemistry of aqua complexes of ruthenium(II) has been investigated in great detail by Meyer, 37 Che, 41 and Takeuchi. 42 Thus, the aqua complex [RuCl(OH 2 )(1a-κ 4 P,N,N,P)] + (3a) is possibly related to the hypothetical ruthenium(IV) oxo species [RuCl(O)(1a-κ 4 P,N,N,P)] + , the putative intermediate in the catalytic epoxidation described below.…”
Section: Resultsmentioning
confidence: 99%
“…31 P NMR (101 MHz,CDCl3): δ -15.2 (s) (δ -16.5 was reported for (rac)-1c). 18 MS (EI): m/z 829 (M + , 98), 751 ([M -Ph] + , 40), 540 ([M -NdC-PPh2] + , 100). Other analytic and spectral data are as in ref 20.…”
Section: Methodsmentioning
confidence: 99%
“…The infrared spectra of the dinuclear complexes [13] Table 2. The dinuclear complex [18](PF 6 ) 2 shows a typical piano-stool geometry for the ruthenium atoms with the metal centers being coordinated by the aromatic ligand, a terminal chloride and a chelating N,N-ligand (Fig.…”
Section: Characterization Of the Dinuclear Complexesmentioning
confidence: 99%
“…In many cases the charge transfer properties of these compounds justify this interest. Especially with these nitrogen donor ligands have been shown to be effective catalysts for oxidation reactions [11][12][13][14][15][16][17][18][19] and for ringopening metathesis polymerization [20] and recent studies of arene ruthenium complexes have shown that they are found to inhibit cancer cell growth [21][22][23][24][25][26], as non-linear optical (NLO) materials [27,28]. For a majority of the complexes studied, the metal centers are linked by a bridging ligand and the nature of the bridge has a fundamental influence on the electronic interaction between the metals and therefore on the characteristics of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Ruthenium complexes containing nitrogen donor ligands have been shown to be effective catalysts for oxidations reactions [1][2][3][4][5][6][7][8][9], and the ruthenium compound with oxazoline molecules have been shown to tune the properties of a metal catalyst [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%